Determining a clinically relevant strategy for bone tissue engineering: an "all-in-one" study in nude mice. - Pierre Corre; Christophe Merceron; Caroline Vignes; Sophie Sourice; Martial Masson; Nicolas Durand; Florent Espitalier; Paul Pilet; Thomas Cordonnier; Jacques Mercier; Séverine Remy; Ignacio Anegon; et al. (PLoS ONE, 2013)
PURPOSE: Autologous bone grafting (BG) remains the standard reconstruction strategy for large craniofacial defects. Calcium phosphate (CaP) biomaterials, such as biphasic calcium phosphate (BCP), do not yield consistent results when used alone and must then be combined with cells through bone tissue engineering (BTE). In this context, total bone marrow (TBM) and bone marrow-derived mesenchymal stem cells (MSC) are the primary sources of cellular material used with biomaterials. However, several other BTE strategies exist, including the use of growth factors, various scaffolds, and MSC isolated from different tissues. Thus, clinicians might be unsure as to which method offers patients the most benefit. For this reason, the aim of this study was to compare eight clinically relevant BTE methods in an "all-in-one" study. METHODS: We used a transgenic rat strain expressing green fluorescent protein (GFP), from which BG, TBM, and MSC were harvested. Progenitor cells were then mixed with CaP materials and implanted subcutaneously into nude mice. After eight weeks, bone formation was evaluated by histology and scanning electron microscopy, and GFP-expressing cells were tracked with photon fluorescence microscopy. RESULTS/CONCLUSIONS: Bone formation was observed in only four groups. These included CaP materials mixed with BG or TBM, in which abundant de novo bone was formed, and BCP mixed with committed cells grown in two- and three-dimensions, which yielded limited bone formation. Fluorescence microscopy revealed that only the TBM and BG groups were positive for GFP expressing-cells, suggesting that these donor cells were still present in the host and contributed to the formation of bone. Since the TBM-based procedure does not require bone harvest or cell culture techniques, but provides abundant de novo bone formation, we recommend consideration of this strategy for clinical applications.